PP.05.27: ARTERIAL STRUCTURAL AND FUNCTIONAL EFFECTS OF INCRETIN THERAPY IN TYPE 2 DIABETES MELLITUS PATIENTS. (June 2015) - Maloberti, A.; Cimino, E.; Casati, M.; Villa, P.; Cairo, M.; Macchiarulo, M.; Frara, S.; Spreafico, E.; Gamba, P.; Pincelli, A.I.; Bombelli, M.; Grassi, G.
Abstract : Objective: The introduction of Incretin Therapy (IT - GLP-1 analogous and DPP-IV inhibitors) has determined an important change in the therapeutic approach to type 2 Diabetes Mellitus (DM2). Along with a better glycemic control, extra-glycemic properties have been observed such as a reduction in blood pressure (BP), weight and cholesterol. Whether these properties can be accounted for an overall effect of the drug on cardiovascular target more favorable than traditional approaches is still unknown and studies are currently ongoing in order to evaluate surrogate markers of arterial diseases. The present study is aimed at assessing arterial function and structure in 30 DM2 patients at time 0 and after 6 and 12 months from the initiation of IT. Design and method: We analyzed preliminary data belonging to the first 8 patients enrolled in the study at time 0 and 1 (58.4 ± 10.3years; female 37.5%). Measurements included anthropometric variables, office and ambulatory (ABPM) systolic (S) and diastolic (D) BP, blood glucose, HbA1C, serum lipid variables. Arterial properties were assessed by the analysis of Pulse Wave Velocity (PWV, complior), Pulse Wave Analysis (PWA, Sphygmocor), Carotid Distensibility (Esaote-WTS), carotid Intima Media Thickness (IMT, Esaote-WTS) while endothelial function was assessed by Flow Mediated Dilation (FMD, Esaote-WTS). Results: At time 1 we observed a not statistically significant trend to an improvement in glycemic control (HbA1c 7.6 ± 0.8 vs 6.7 ± 0.5%; p = ns) associated with a reduction in office SBP (135.1 ± 18.2 vs 127.1 ± 17.3mmHg; p = 0.04) while DBP, BMI and serum lipids did not change. Accordingly Aortic SBP and PP decrease significantly (122.1 ± 14.9 vs 113.1 ± 12.1mmHg, p = 0.04; 46.5 ± 13.5 vs 37.7 ± 11.3mmHg, p = 0.001) while ABPM measurement were superimposable at follow-up. Arterial markers didn't shown any significant changes in the 6 months of observation but carotid distensibility improve from 1.6 ± 0.9 to 2.8 ± 1.2 with a P value close to statistical significance (P = 0.058). Conclusions: The preliminary results of the present study suggest that 1) IT therapy reduces office SBP but not ambulatory BP and that 2) this effect is associated with a clear tendency of improvement in arterial distensibility.